BIOACTIVE TERPENOID FROM THE BALINESE NUDIBRANCH Hypselodoris infucata - Martiningsih, Ni Wayan; Prasetia, I Nyoman Dodik; Nursid, Muhammad; Mudianta, I Wayan (Indonesian Journal of Pharmacy, 2016)
Marine organisms, in particular nudibranchs (Mollusca: nudibranchia), are known as a rich source of chemically diverse secondary metabolites exhibiting potential as antimalarial, anti-inflammatory, antiviral and anticancer activity. We presented the chemical investigation of an extract of nudibranch Hypselodoris infucata collected from Bali, an unexplored water but rich in nudibranch diversity. The extract contained the known (â€“)-furodysinin (1), a furanosesquiterpene that for the first time isolated from this species. Metabolite 1 was purified by chromatography and the structure was characterised by comparison of 1H NMR data with that of the reported data. The absolute configuration was determined by comparing the optical rotation values with the known enantiomer. In vitro cytotoxic activity of compound 1 against HeLa cell line displayed an IC50 at 102.7Âµg/mL. We also report for the first time the development of a method to assay nudibranch extracts for their feeding deterrence activity against local shrimps Penaeus vannamei. The extract show food rejection with highly significant difference in respect to the control (P = 0.0061) at natural concentration of 3.0mg/mL.Keywords: nudibranch, natural product, feeding deterrence, Hypselodoris